Cluster Analysis Using Hierarchic Method for Classification of District / City of North Kalimantan Province Based on Human Development Indicators (HDI) - Rizal, Muhammad; Fadhila, Shofia Nur; Prihantini (Proceeding International Conference on Science and Engineering, 2021)
Abstract. HDI is an important indicator in measuring the success of the development of the quality of human life in terms of education, health, and life worthiness. HDI in the province of North Kalimantan (Kaltara) has always experienced a significant increase. However, the increase is always below the national figure. This is due to the development that is not implemented evenly and is not on target. Cluster analysis is a multivariate method that has the aim of grouping, where a group has relatively the same characteristics (homogeneous), while between groups has different characteristics. This study showed that the best method in hierarchical cluster analysis is the ward's method. Therefore, there were 4 clusters in the HDI in North Kalimantan province which included HDI with the high category, namely the city of Tarakan, then the HDI with the medium category, namely Malinau district then the HDI with the low category namely Bulungan district, then the HDI with the very low category namely Tanah Tidung district and Nunukan district.